MEF2C promotes gefitinib resistance in hepatic cancer cells through regulating MIG6 transcription. Issue 3 (June 2018) - Zhang, Hui; Liu, Wei; Wang, Zhi; Meng, Lin; Wang, Yunhua; Yan, Huawu; Li, Lin
Introduction: Mitogen-inducible gene 6 ( MIG6 ) holds a special position in epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) resistance. As MIG6 regulates the activity of EGFR signal pathway negatively, high level of MIG6 can increase the EGFR TKI resistance of cancer cells, and limit the therapeutic action of EGFR TKI, such as gefitinib or erlotinib. Therefore, better understanding of the molecular mechanisms underlying the regulation of EGFR TKI resistance holds great value in cancer therapy. Methods: In our study, we mainly explored the function of transcription activator, myocyte enhancer factor 2C (MEF2C), on MIG6 expression as well as gefitinib-resistant ability of hepatic cancer cells. Results: Our results indicated that both MEF2C and MIG6 could be upregulated in gefitinib-resistant cancer tissues and cancer cell lines compared with gefitinib-sensitive ones. Chromatin immunoprecipitation assay and dual luciferase assay showed that MEF2C could bind to the MEF2C element in the promoter sequence of MIG6 and promote the transcription of MIG6. This effect increased the gefitinib-resistant ability of cancer cells. Therefore, MEF2C knockdown inhibited the gefitinib resistance and limited the proliferation of hepatic cancer cells in vitro and in vivo, while overexpression of MEF2C showed opposite effect on cancer cell proliferation. Conclusion: Our study provides novel insight into the regulation mechanism of MIG6 and suggests potential implications for the therapeutic strategies of gefitinib resistance through inhibiting MEF2C in hepatic cancer cells.